Difficulties of applying the continuous evaluation to the upper primary students from the point of view of teachers in Saudi Arabia - Alshammari, Mohammed khzaiyem Omeer (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the difficulties of applying the continuous evaluation to the upper primary students from the point of view of the teachers in Hafr Al-Batin governorate in the Kingdom of Saudi Arabia.The study population consisted of all teachers of the upper grades in all the primary schools for the first semester of the academic year 1440/1439 AH – 2018/2019, (432) teachers. The study sample consisted of (354) teachers who responded to the questionnaire and make up 82% studying. The study data were collected using a questionnaire designed specifically for the purposes of the study. The study found that there are difficulties in the application of continuous evaluation due to the lack of incentives provided to teachers, crowded students in the classroom, and low awareness of parents of their role in the continuous evaluation. The study also recorded the absence of a statistically significant difference in the teachers' response due to the experience variable, while there is a statistically significant difference attributed to the specialization variable.
Keywords: difficulties; continuous evaluation; teachers; the upper primary